Attitudes to food and weight : a survey in a women's residence at the University of Cape Town - Robinson, Christopher John (Department of Psychology, 2015)
Epidemiological research in the past decade has indicated that clinical and subclinical eating disorders are widespread amongst the female population of many Western countries. Following an introductory overview of some of the literature on anorexia nervosa and bulimia, highlighting the lack of diagnostic clarity in this area, previous epidemiological findings are reviewed. The eating attitudes and dietary behaviour of a female student population in a residence at the University of Cape Town are then detailed. The sample comprised 123 women, shown to be a representative sample of the residence population, and data were collected by means of the Eating Attitudes Test (Garner and Garfinkel, 1979). Results indicate that 13.8% of the sample population scored above the threshold score of 30 on this test; results are discussed with particular focus on specific attitudes and behaviours possibly indicative of anorexic or bulimic symptomatology, and which are elicited by EAT responses. Clinical interviews were conducted with those women who scored over 30 and who supplied their names (9 students); qualitative data obtained from these interviews augment the quantitative analysis of the EAT data, particularly with respect to the phenomenon of binge-eating behaviour. Findings of the present study accord overall with results obtained elsewhere amongst similar populations. The study does, however, call into question presently held assumptions about the nature of binge-eating, and the diagnostic criteria for anorexia nervosa and bulimia.